SURVEI MOTIVASI BELAJAR SISWA DALAM MENGIKUTI PENDIDIKAN JASMANI MELALUI AKTIVITAS PERMAINAN KECIL DI SMPLB MANUNGGALSLAWI KAB.TEGAL TAHUN 2012 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This research problem is how to motivate students attend physical education through the activities of small game in SMPLB Manunggal Slawi. The purpose of research to determine the student’s motivation to attend physical education through a small gaming activities SMPLB Manunggal Slawi in 2012. Variable study student’s motivation to attend physical education through the activities of small game.Collecting data using a scale of motivation research and further analyzed using descriptive formula percentage. The results showed that intrinsic factors of students in physical education followed by a small gaming activities SMPLB Manunggal Slawi in 2012 to influence motivation in participating in physical education in the high category (78.26%), while extrinsic factors also can influence motivation in participating in a physical education class moderate (69.59%). So the high influence of intrinsic factors on students’ motivation due to the physiological needs of the students had high (52.17%), have a high need for security (78.26%), have a high self-actualization needs (69.57%). ABSTRAKPermasalahan penelitian ini adalah bagaimana motivasi belajar siswa mengikuti pendidikan jasmani melalui aktivitas permainan kecil di SMPLB Manunggal Slawi. Tujuan penelitian untuk mengetahui motivasi siswa dalam mengikuti pendidikan jasmani melalui aktivitas permainan kecil di SMPLB Manunggal Slawi tahun 2012. Variabel Penelitian ini motivasi siswa dalam mengikuti pendidikan jasmani melalui aktivitas permainan kecil . Pengumpulan data penelitian menggunakan skala motivasi dan selanjutnya dianalisis menggunakan rumus deskriptif persentase. Hasil penelitian menunjukan bahwa faktor intrinsic  siswa dalam mengikuti pendidikan jasmani melalui aktivitas permainan kecil di SMPLB Manunggal Slawi tahun 2012 mampu mempengaruhi motivasinya dalam mengikuti pendidikan jasmani dalam kategori tinggi (78,26%) sedangkan faktor ekstrinsik juga mampu mempengaruhi motivasinya dalam mengikuti pendidikan jasmani dalam kategori sedang  (69,59%).